Sublingual microcirculatory alterations in cirrhotic patients. (16th April 2018) - Gonzalez Ballerga, Esteban; Pozo, Mario O.; Rubatto Birri, Paolo N.; Kanoore Edul, Vanina Siham; Sorda, Juan A.; Daruich, Jorge; Dubin, Arnaldo
Abstract: Objective: To assess sublingual microcirculation in cirrhotic patients and its relationship to spider angiomas, complications, and outcome. Methods: Thirty‐one cirrhotic patients were prospectively compared to 31 matched controls. Sublingual microcirculation was evaluated by videomicroscopy. We specifically looked for capillaries with increased RBCV, which was defined as a velocity higher than the percentile 100th of controls. Results: Compared to controls, cirrhotic patients showed decreased total and PVD (14.4 ± 2.2 vs 16.0 ± 1.3 and 14.1 ± 2.3 vs 15.9 ± 1.6 mm/mm 2, respectively, P  <   .001 for both) and increased HFI (0.64 ± 0.39 vs 0.36 ± 0.21, P  =   .001). They also exhibited high RBCV in 2% of the microvessels ( P  <   .0001). Patients with MELD score ≥10 had higher RBCV than patients with score <10 (1414 ± 290 vs 1206 ± 239 μm/s, P  <   .05). Patients with spider angiomas showed lower vascular densities. Microcirculation did not differ between survivors and nonsurvivors. Conclusions: Cirrhosis is associated with microcirculatory alterations that can be easily monitored in the sublingual mucosa. Alterations included decreased density and PPV and hyperdynamic microvessels. The most striking finding, however, was the microvascular heterogeneity. Patients with spider angiomas had more severe alterations. Larger studies should clarify the relationship between microcirculatory abnormalities and outcome.